Animal models of systemic sclerosis: their utility and limitations - Artlett CM (Dove Medical Press, 2014)
Carol M Artlett Department of Microbiology and Immunology, Drexel University College of Medicine, Philadelphia, PA, USA Abstract: Without doubt, animal models have provided significant insights into our understanding of the rheumatological diseases; however, no model has accurately replicated all aspects of any autoimmune disease. Recent years have seen a plethora of knockouts and transgenics that have contributed to our knowledge of the initiating events of systemic sclerosis, an autoimmune disease. In this review, the focus is on models of systemic sclerosis and how they have progressed our understanding of fibrosis and vasculopathy, and whether they are relevant to the pathogenesis of systemic sclerosis. Keywords: systemic sclerosis, animal models, vasculopathy, fibrosis, chicken, mouse